Is urgent surgical management necessary for priapism in pediatric patients with hematologic conditions?. Issue 4 (August 2022) - Patel, Sagar R.; Reddy, Amit; Dai, Michelle; Passoni, Niccolo; Khera, Mohit; Koh, Chester J.
Summary: Introduction: Acute priapism is usually considered a medical emergency that warrants prompt urologic evaluation and treatment. Efforts have been made to determine the optimal management strategy for pediatric priapism. Objective: The aim of this study is to assess differences in conservative, minimally-invasive, and operative management of acute priapism in the pediatric population. Study design: A retrospective study of pediatric patients with acute priapism from 2015 to 2021 at a single tertiary care children's hospital was conducted. Conservative, minimally-invasive, and operative approaches for the priapism episodes during these hospital encounters were analyzed. Results: Thirty-nine patients were identified with a total of 61 cases of acute pediatric priapism were evaluated in the study period. Eight-three percent of patients were African-Americans, and 72% of patients had a history of sickle cell disease. Oxygen therapy (P = 0.001) and hydration with intravenous fluids (P = 0.00318) were more commonly utilized for hematologic-associated cases compared to other etiologies. For priapism episodes of hematologic etiology, 18 (40.0%) and 18 (40.0%) patients received phenylephrine injection and aspiration/irrigation (e.g., minimally-invasive therapy), respectively, while for the other causes of priapism, three (18.8%) and four (25.0%) received phenylephrine injection and aspiration/irrigation (e.g., minimally-invasive), respectively. Conservative and minimally-invasive treatment resulted in complete resolution of priapism in 27 (60%) and 16 (35.5%) patients with hematologic-associated priapism while 12 (75%) and 1 (6.3%) patients with other etiologies had resolution of priapism with conservative and minimally-invasive treatment, respectively. One patient received shunting in the hematologic group while two patients received shunting in the non-hematologic group (P = 0.1031). Discussion: Hematologic disorders are the most common causes of priapism in children and adolescents. An overwhelming majority of priapism events in the pediatric population can be managed with conservative therapies including oxygenation and intravenous hydration as well as minimally-invasive procedures such as corporal aspiration, irrigation and/or injections. The utilization of corporal shunting, anesthesia, and hospital resources is infrequently necessary for pediatric priapism episodes. Conclusion: While urgent surgical management is often performed in the adult population, a minimally-invasive management strategy can be implemented in the pediatric population where an extended period of conservative management that avoids operative management and general anesthesia is effective. Summary Table Management strategies and resolution rates of acute pediatric priapisms based on hematologic and non-hematologic etiologies. Summary Table   Total Hematologic Other P-value Cases 61 45 16   Penile Ultrasound 6 2 4 0.01778 Corporal Blood Gas 6 5 1 0.57548 Nasal Canula 25 24 1 0.001 Intravenous Fluids 44 37 7 0.00318 Transfusion 1 1 0 0.5485 Conservative Therapy  Resolution of Priapism 39 27 12 0.2872 Minimally Invasive Intervention  Phenylephrine Injection 0 0 0 0.5485  Aspiration/Irrigation 2 1 1 0.4354  Both 20 17 3 0.16452  Resolution of Priapism 17 16 1 0.0230 Operative Management  Aspiration/Irrigation 2 1 1 0.4354  Shunting 3 1 2 0.1031  Resolution of Priapism 5 2 3 0.0731 Anesthetic  Ketamine 4 4 0 0.2187  Midazolam 4 3 1 0.95216  General Anesthesia 5 2 3 0.07346 Medication of Stuttering Priapism  Pseudoephedrine 18 18 0 0.00544  Ketoconazole 3 3 0 0.28914